2018
DOI: 10.1371/journal.pone.0199644
|View full text |Cite
|
Sign up to set email alerts
|

Using citizen science to describe the prevalence and distribution of tick bite and exposure to tick-borne diseases in the United States

Abstract: Tick-borne pathogens are increasing their range and incidence in North America as a consequence of numerous factors including improvements in diagnostics and diagnosis, range expansion of primary vectors, changes in human behavior, and an increasing understanding of the diversity of species of pathogens that cause human disease. Public health agencies have access to human incidence data on notifiable diseases e.g., Borrelia burgdorferi, the causative agent of Lyme disease, and often local pathogen prevalence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 46 publications
4
85
0
Order By: Relevance
“…For instance, we detected Powassan virus in 1.8% of ticks, while previous studies have detected this virus in 1.3 and 4.6% of ticks [ 62 , 63 ]. We detected A. phagocytophilum in 10.7% of ticks, and previous studies have detected this organism in 2.5–14% of ticks [ 64 , 66 , 68 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…For instance, we detected Powassan virus in 1.8% of ticks, while previous studies have detected this virus in 1.3 and 4.6% of ticks [ 62 , 63 ]. We detected A. phagocytophilum in 10.7% of ticks, and previous studies have detected this organism in 2.5–14% of ticks [ 64 , 66 , 68 ].…”
Section: Discussionsupporting
confidence: 73%
“…We validated our NGS results by PCR and also found good concordance between our results and those of previous studies of ticks from the same region. The pathogens we detected had all been previously observed in Wisconsin, and our measures of prevalence were in the ranges previously reported [ 4 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. For instance, we detected Powassan virus in 1.8% of ticks, while previous studies have detected this virus in 1.3 and 4.6% of ticks [ 62 , 63 ].…”
Section: Discussionsupporting
confidence: 73%
“…This cluster of cases is in an area where A americanum is not included in the CDC map of the tick territory, though there have been occasional reports according to the Minnesota Department of Health (https://www.health.state.mn.us/) and a recent citizen science intitiative. 26 Of 59 allergists who provided information about the effectiveness of dietary avoidance in relation to allergic symptoms, 49 (83%) reported that more than 90% of their patients became free from allergic attacks by avoiding mammalian meat. An additional 15% of providers reported that at least 70% of their patients responded to mammalian meat avoidance, with some of these providers mentioning that dairy avoidance was additionally required for a minority of their patients.…”
Section: The Epidemiology Of A-gal Syndrome In the United Statesmentioning
confidence: 99%
“…Tick-borne infections are on the rise in the USA and Europe due to a host of different factors including climate change (5,6) and disruption of predator density in suburban areas (7). Recent studies on tick prevalence and pathogen load have identified new geographical areas where vector ticks are present (8), as well as novel tick-borne pathogens present in areas where they had not previously been identified (such as B. miyamotoi in Northern California) (9). Lyme disease can affect many different body systems and organs (10).…”
Section: Introductionmentioning
confidence: 99%